2014
DOI: 10.1149/2.0311409jes
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and Simulations of Electrochemical Impedance Spectroscopy of a Three-Electrode Coin Cell Design for Li-Ion Cell Testing

Abstract: A 2-D mathematical model of the secondary current distribution in a three-electrode cell is used in order to understand distortion of impedance spectra influenced by the position of the reference electrode (RE) in a cell when one electrode extends past the other. The cell setup consists of a modified coin cell, i.e., working and counter electrodes face each other, and a RE is positioned behind the counter electrode (CE) that has a small hole in it to allow for electrolyte access. This configuration shows large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…13 Yet, experiments and numerical simulations by Ender et al 14 showed that the impedance measurements with the latter reference electrode placement can display significant distortions caused by small in-plane offsets between anode and cathode (referred to as geometrical asymmetry) and/or by large differences in the impedance response of anode and cathode (referred to as electrical asymmetry), consistent with earlier work by Dees et al 15 This is also the case for coaxially located reference electrodes, for which the measured anode or cathode impedance is shown to be highly sensitive toward misplacements of the electrodes. 10,12,16 * Electrochemical Society Student Member. * * Electrochemical Society Fellow.…”
mentioning
confidence: 99%
“…13 Yet, experiments and numerical simulations by Ender et al 14 showed that the impedance measurements with the latter reference electrode placement can display significant distortions caused by small in-plane offsets between anode and cathode (referred to as geometrical asymmetry) and/or by large differences in the impedance response of anode and cathode (referred to as electrical asymmetry), consistent with earlier work by Dees et al 15 This is also the case for coaxially located reference electrodes, for which the measured anode or cathode impedance is shown to be highly sensitive toward misplacements of the electrodes. 10,12,16 * Electrochemical Society Student Member. * * Electrochemical Society Fellow.…”
mentioning
confidence: 99%
“…REs are commonly used in various areas of electrochemistry, but the close proximity of lithium-ion cell electrodes and the low conductivity of electrolytes (compared to aqueous systems) make it difficult to introduce a reliable third electrode. Several three-electrode configurations [1][2][3][4][5][6][7] have been employed for lithium-ion studies, including the following: i) T-cell set-up where the RE is positioned at the edge of the electrode sandwich ii) a Swagelok-cell design, where a coaxial micro-RE is position at each side of the cell sandwich with holes in both the working electrode (WE) and CE; (iii) a coin-cell * Electrochemical Society Member.…”
mentioning
confidence: 99%
“…However, a reliable 3-electrode setup can be experimentally challenging, considering cell design and referenceelectrode positioning. [31][32][33][34] Hence, the purpose of this section is to assess the error made by using 2-electrode data as an input for a 3-electrode based model analysis by fitting 2-electrode surrogate data simulated from the P2D model with the basecase 3-electrode P2D model. The difference between the two models is that the WE potential is either referred to the CE or the RE.…”
Section: Resultsmentioning
confidence: 99%